The end of art as a capitalist discourse Kapitalist bir söylem olarak sanatın sonu - Samsun, Meysem (Journal of Human Sciences, 2015)
In the present paper, the claim, art or painting is going through its end, is evaluated as a capitalist discourse; and some related samples were analyzed in terms of how they were passivized and become dysfunctional by the capitalist system. French thinker Jean Baudrillard is the most effective and distinguished sample of the claim, the end of art. In this point, after evaluating Danto’s ideas from the modern perspective, the claim of “end of art” will be discussed through Baudrillard’s post-modern perspective. When Baudrillard directed his gaze onto the world of art, the situation he saw was not a very optimistic one. Modern art and post-modern art, in which the thinker is also included, is the production of the Western World. As a result, in this sense, the literature of art is merely valid for the modern art taking its roots from the Western World and this domain of thinking. According to Baudrillard, art has lost its own privilege and purpose; it is not made for development of culture, but for consumption of this culture; and instead of existing through its own content of meaning, it has been unconsciously spread over all segments of the society. As a result, the discussion of what is art and what is not has progressively become more ambiguous. Özet Bu çalışmada sanatın ya da resmin sonunun geldiği savı kapitalist bir söylem olarak değerlendirilmiş, sanatın kapitalist sistem tarafından nasıl edilgen ve işlevsiz kılındığına ilişkin örneklendirmelerle işlenmiştir. Sanatın sonu sav’ının, bu örneklendirme ile, en etkili duayen ismi Fransız düşünür Jean Baudrillard’dır. Burada, modern anlamda Danto’nun görüşlerine yer verildikten sonra ‘’sanatın sonu’’ savı, postmodern anlamda, Baudrillard üzerinden tartışılacaktır. Baudrillard bakışını sanat dünyasına çevirdiğinde gördüğü manzara iç açıcı değildir. Burada bahsedilen çağdaş sanat, postmodern sanat, düşünürün de içinde bulunduğu Batı dünyasının üretimidir. Dolayısıyla, bu bağlamda literatür, sadece Batı dünyası ve bu düşünce dünyasından beslenen çağdaş sanat için geçerlidir. Baudrillard’a göre sanat artık sahip olduğu ayrıcalığı ve amacını yitirmiş, kültürü geliştirmek için değil, tüketilmek için yapılmış ve kendi anlam içeriği ile var olmak yerine toplumun tüm katmanlarına bilinçsizce yaydırılmış ve neyin sanat olup neyin sanat olmadığı tartışmaları iyice bulanıklaşmıştır.